Rebranding Ilegal: Tinjauan Hukum Etika Bisnis dan Unsur Perbuatan Melanggar Hukum Ditinjau Melalui Perspektif Perlindungan Konsumen - Gita Ananda Putri Maylendra; Teddy Prima Anggriawan (CV Rewang Rencang, 2025)
Rebranding is a business activity carried out by business actors to make changes with the aim of improving the company's image. Rebranding becomes a problem when the rebranding is done illegally. Illegal rebranding activities by business actors not only affect intellectual property, but also consumers as product user. In the legal context, illegal rebranding can be categorized as an unlawful act because it can cause harm to consumers as stated in Article 1365 of the Burgerlijk Wetboek. Whereas business actors in carrying out business activities must implement business ethics and good faith. The results of this study show the importance of consumer protection in overcoming the problem of illegal rebranding.